Transport and Retention of K(+) and Other Metabolites in a Marine Pseudomonad and Their Relation to the Mechanism of Optical Effects - Matula, Tibor I. (1970)
Suspensions of cells of a marine pseudomonad washed with 0.05 m MgSO(4) showed an immediate increase in optical density (first-phase optical change) when the salt concentration of the suspending medium was increased; a subsequent slow decrease in optical density (second-phase optical change) occurred if K(+) was present. The rate of the second-phase change was similar to the rate of uptake of (42)K(+) by the cells. Glutamate increased the rate and extent of the second-phase change and produced a parallel increase in the rate and extent of uptake of (42)K(+). Citrate increased the extent of the second-phase change in cells adapted to oxidize citrate but not in unadapted cells. Adapted, but not unadapted, cells accumulated (14)C-citrate. The nonmetabolizable α-aminoisobutyric acid (AIB) also increased the extent of the second-phase change under conditions leading to the uptake of (14)C-AIB by the cells. Cells maintained in a salt solution optimal for the retention of intracellular solutes were found to contain 0.184 m K(+). In the same salt solution, cells preloaded with (42)K(+) retained the isotope, but they lost it rapidly when suspended in 0.05 m MgSO(4). The second-phase changes can be accounted for by the energy-dependent accumulation in an osmotically active form of K(+) and other metabolites by cells depleted of intracellular solutes.